Pengembangan Komik Mitigasi Berbasis Potensi Bencana Lokal yang Terintegrasi dalam Pembelajaran Fisika di Sulawesi Tengah - Fittri Yani; Unggul Wahyono (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2020)
This study aims to produce appropriate learning media in supporting the implementation of learning about disaster mitigation. The type of research used is Research and Development (R&D) and uses the 4D development model namely Define, Design, Develop and Disseminate. After becoming a product, it is then validated by material experts and media experts. The results of the material expert validation obtained an average score of 3,13 in the "good" category and the media expert validation obtained an average score of 3,50 with the "very good" category. The comic that has been validated by several experts is then revised by the researcher by referring to the advice given by the validator. To make this comic, researchers used the CorelDRAW X8 application. The subjects of this comic mitigation feasibility trial were class VIII students of SMP Negeri 10 Palu. The average score obtained is 3,56 with the category "strongly agree". The conclusion in this study is that the mitigation comics developed can be used as a media to support disaster learning integrated in physics learning.